LGBTQ in the 21st century - H.W. Wilson Company (Amenia, New York : Grey House Publishing, 2017)
Issues explored in this title include the role of non-traditional same-sex families, and expanded protections for transgender people under the framework of civil rights. The acronym LGBTQ, standing for lesbian, gay, bisexual, transgender, and queer, is an acronym created to refer to a broad group of people, living around the world and coming from a wide variety of different creeds and cultures, whose behavior is seen as "nonconformist" with regard to mainstream concepts of gender and sexuality. For most of history, those who failed to conform with mainstream ideas about gender and sexuality were forced to hide their behavior or face social and legal penalties that could even include execution. Over time, LGBTQ people have fought for equal rights under the law and the right to express their sexuality or gender without reprisal. The primary issues in the United States surrounding LGBTQ individuals concern the degree to which individuals have the right to determine their own gender and sexual identity and whether other individuals have the right to discriminate against LGBTQ individuals based on their cultural, religious, or personal beliefs. - Publisher/Preface.
1. LGBTQ and the Law -- Legalizing Identity: LGBTQ Rights and Laws -- Onslaught of Anti-LGBT Bills in 2017 Has Activists "Playing Defense" / Susan Miller -- The Equality Act is Essential in the Fight for LGBTQ Rights / Michelle Chen -- U.S. Court Rules 1964 Civil Rights Law Protects LGBT Workers from Bias / Reuters -- No, LGBTQ Americans Aren't in the Clear after Trump's Religious Liberty Order / Michelangelo Signorile -- What Kentucky's Religious Freedom Bill Could Mean for LGBTQ Students / Iman Smith -- The Many Dreadful Ways That the Trump Administration Will Hurt LGBTQ Health Care / Daniel Summers -- In Conservative America, Small Cities Stand up for LGBT Rights / Letitia Stein -- In Religious Freedom Debate, Two American Values Clash / Tom Gjelten -- Trans Activist Sarah McBride to Make History at DNC / Emma Margolin -- 2. LGBTQ and the World -- The Global Perspective: LGBTQ Rights Around the World -- Most Countries Score an F on Our LGBT Human Rights Report Card / Susan Dicklitch-Nelson and Berwood Yost -- Ontario's Multiparent LGBTQ Families Have Another Reason to Celebrate This Season / Alison Motluk -- Time to Panic / Masha Gessen -- The Coming Islamic Culture War / Daveed Gartenstein-Ross and Nathaniel Barr -- U.N. Experts Condemn Killing and Torture of Gay Men in Chechnya / Sewell Chan -- 3. LGBTQ Culture -- Culture in Evolution: LGBTQ People in Society -- "Discrimination is Doing its Dirty Work": A New Survey Looks at the Effects of Anti-LGBTQ Hate / German Lopez -- Is It Time We Agreed on a Gender-Neutral Singular Pronoun? / Gary Nunn -- The Gender Identity Terms You Need to Know / Cydney Adams -- Corporate America's Evolution on L.G.B.T. Rights / Richard Socarides -- Exclusive: Gay Man Explains His Petition to "Drop the T" in LGBT / David Marcus -- Infinite Identities / Katy Steinmetz -- Transgender Issues Are Driving a Wedge in LGBT Community, Says Activist Ousted from Pride Parade / Bryan Polcyn and Stephen Davis -- Why the Trump Administration Won't Ask about LGBT Americans on the 2020 Census / Emma Green -- 4. LGBTQ in the Schools -- Teaching and Learning Gender and Sexuality: LGBTQ in the Schools -- A Letter from an Ivy League Admissions Dean / James Freeman -- Could Betsy DeVos Be an Ally for Transgender Students? It's Complicated / Story Hinckley -- Minnesota Kindergarten Students Forced to Confront Gender Identity / Kelsey Harkness -- LBGT Students Are Not Safe at School / Marissa Higgins -- California Approves LGBT history Lessons for Classrooms / Associated Press -- 5. LGBTQ and the Family -- Family Matters: LGBTQ Parenting and Families -- Texas Poised to Allow Adoptions to Be Blocked on Religious Basis / Ian Lovett -- This Is What It's Like to Raise a Gender-Neutral Child / Bo Hanna -- I'm a Gay Parent, Still Trying to Find My Identity in the LGBTQ Community / Amber Leventry -- Why Raising a Gender Neutral Child is a Terrible Idea / Rachel Lu -- How Paid Leave Policies Can Negatively Affect LGBTQ Families / Rebecca Gale -- For Many Queer Adults, Parenting Still Isn't Part of the Picture / John Culhane -- Reimagining What Families Can--and Do--Look Like / Elizabeth Morehead.
Includes bibliographical references (pages 175-181) and index.
Keywords: Sexual minorities -- United States; Sexual minorities -- Civil rights -- United States; Sexual minorities -- United States -- 21st century -- Sources; Sexual minorities -- Civil rights -- United States -- 21st century -- Sources; Lesbians -- United States -- 21st century -- Sources; Gay people -- United States -- 21st century -- Sources; Bisexual people -- United States -- 21st century -- Sources; Transgender people -- United States -- 21st century -- Sources; Sexual minority community -- United States -- 21st century -- Sources; Sources